UNIVERSAL CODING SYSTEM FOR PALEONTOLOGICAL COLLECTIONS AS AN EFFECTIVE BASIS FOR CREATING A UNIFIED ELECTRONIC COLLECTIONS CATALOG AT THE INSTITUTE OF GEOLOGICAL SCIENCES OF THE NAS OF UKRAINE - Аністратенко, О.Ю.; Вернигорова, Ю.В. (Institute of Geological Sciences, NAS of Ukraine, 2022)
A method of universal coding of paleontological collections is proposed. It is aimed to organize a uniform electronic catalog of various geological collections of the Institute of Geological Sciences of the National Academy of Sciences of Ukraine (IGS NAS of Ukraine). The problems of arranging the data of the natural scientific collections in Ukraine and the peculiarities of the arrangement of paleontological collections of IGS NAS of Ukraine were considered. The absence of a unified template for labeling of paleontological collections of IGS NAS of Ukraine has been stated. This encourages us to elaborate of a convenient universal coding system for the systematization of existing and newly created paleontological collections. The proposed coding of paleontological collections is based on the unified principle of using universal abbreviations in Latin letters. The coding system consists of a full code, a short code, and a universal label. The full code is intended for coding the collection’s general characteristics and subsequent use in compiling the universal electronic catalog. The short code is needed for marking an individual specimen within any collection. The universal collection label is a necessary component in the design and storage of a collection, as it carries basic information. It also has an additional reference about the collection and contains information that is also used when compiling electronic catalogs of collections. The developed coding system is universal and maximally effective in ensuring the uniformity of the code of any collections of a certain scientific institution. It enables the researcher to code collections independently, protects against duplication of the existing code, and is a simple and convenient way of transferring information to the electronic catalog of collections. Our method greatly facilitates the distribution of information during the direct creation (code writing) of the electronic catalog and is the basis of the search system and sorting information into certain categories. This, in turn, makes it possible to have a multidisciplinary electronic catalog, by which one can find information about existing collections of a certain region, stratigraphic age, a certain paleontological group, or certain geological objects (such as samples from boreholes or outcrops). The adoption of the unified Catalogue strategy will ensure the reliable functioning of the paleontological collections of the IGS NAS of Ukraine, as well as become the basis for documenting new collections in accordance with established methodology. Finally, registering all collections is a small but important step in the direction of Open Science, namely, providing open access to information for the scientific community.